Effect of creep feed supplemented with Bacillus subtilis on growth performance, blood parameters, gut permeability and fecal microbiome in piglets - Safaie, Eva S; Kelly, Ashton L; Kwon, Chan-Ho; Torres, Jannell A; Lee, Ji-Hye; Lindemann, Merlin D; McKinley, Enid T; Hernandez, Samantha; Lourenco, Jeferson M; Jang, Young-Dal (Revista Colombiana de Ciencias Pecuarias, 2025)
Background: Creep feed and B. subtilis supplementation may be beneficial for growth and health of pigs around weaning. Objective: This study was conducted to evaluate the effects of creep feed supplemented with Bacillus subtilis on growth performance, gut permeability, inflammation response, fecal score and microbiome of pigs during pre- and post-weaning periods. Methods: A total of 12 litters were randomly allotted to 3 treatments based on breed, parity, and litter size at d 2-5 of age. Treatments were: 1) Control (CON): no creep feed, 2) CF: creep feed (24% crude protein) without B. subtilis supplementation, and 3) CFB: creep feed with B. subtilis supplementation at 1.88×108 CFU/kg diet. At weaning (22-25 d of age), pigs were moved to the nursery facility within original treatments and fed a common diet in 5 pens per treatment with 5 pigs per pen for 35 d. Results: There were no significant differences in the number of pigs weaned, pig and litter weaning weight, weight gain, and creep feed intake in the suckling period (p>0.38). In the nursery period, the CF group had lower body weight (p=0.05, tendency) and average daily gain (p<0.05) in d 0-21 postweaning compared to the CON group with intermediate values in the CFB group, while no difference was observed in the overall nursery period. No significant differences were observed in average daily feed intake, gain-to-feed ratio and fecal score among dietary treatments in the entire nursery period (p>0.11). There were no differences in fecal E. coli count, serum TNF-α, and diamine oxidase levels (p>0.58). Serum levels of IL-1β at weaning (p<0.05) and d-lactate at d 21 postweaning (p=0.08) were lower in the CFB group than the CON group, with intermediate values in the CF group. Serum urea nitrogen concentrations at weaning were greater in the CON group than the CF group (p<0.05). The CFB group had greater fecal microbial richness than the CON group at d 21 postweaning (p<0.05). Conclusion: Creep feed with high protein content did not improve postweaning growth, while B. subtilis supplementation had potential to enhance postweaning growth, reduce gut permeability and inflammation, and influence fecal microbiome.